Musical instrument care submicroemulsion and method of making same
Patent Information
- Application Number
- CN202611016818.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-09-29
- Estimated Expiration
- 2046-07-09
AI Technical Summary
但是,微乳中乳化剂比例较高达到15%~30%,安全性有待考察
[0024]1. 本发明的乐器养护亚微乳为纳米级乳剂,超小粒径可以显著延缓聚集或分层,使得亚微乳可保持数月甚至数年的物理稳定性,具有热力学稳定性,无絮凝、聚结现象。
Smart Images

Figure CN122521237B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of musical instrument technology, specifically to a musical instrument maintenance submicroemulsion and its preparation method. Background Technology
[0002] The fast pace and high pressure of modern life offer a welcome respite, as the beautiful melodies played on instruments like the guqin, guzheng, erhu, pipa, piano, and violin can effectively relieve stress. Cleaning the instrument's surface, keys, and strings is a crucial aspect of instrument maintenance that requires careful attention. Traditional cloths like cotton, flannel, and microfiber cloths are only suitable for daily cleaning of dust, sweat, and fingerprints, and cannot achieve thorough cleaning. Alcohol or ordinary cleaning agents can corrode the instrument's finish and keycaps, causing irreversible damage. Products containing abrasives, such as some polishing agents and deoxidizers, pose the main risk of thinning the instrument's surface, eventually damaging the protective layer. Furthermore, instrument surfaces require not only cleaning but also maintenance. While fingerboard lemon oil, guqin care cream, and violin cleaning and maintenance oils can deeply clean and nourish wooden components (especially the fingerboard), preventing cracking and showcasing the wood grain, they can easily dissolve or damage the finish. The key to instrument surface maintenance lies in balancing the needs for cleaning and nourishment with the potential risks.
[0003] Microemulsions typically have a particle size of 10–100 nm, are transparent or translucent, and can form spontaneously. They are thermodynamically and kinetically stable systems. For example, the string-care nanoemulsion and its preparation method disclosed in the inventor's previous patent document CN120554858A include: polysorbate 80 and sorbitan stearate 60 as main emulsifiers; glyceryl monostearate, cetyl alcohol, and stearyl alcohol as auxiliary emulsifiers; liquid paraffin and xanthan gum to adjust consistency; chitosan-loaded sodium hyaluronate nanoparticles as long-lasting moisturizers; glycerin and propylene glycol as moisturizers and also as antifreeze agents; ethylparaben as a preservative; and optional fragrances. The remainder is water, and the emulsion particle size distribution ranges from 3 to 100 nm. However, the proportion of emulsifiers in microemulsions is relatively high, reaching 15%–30%, and their safety needs to be investigated. Ordinary emulsions typically have a particle size of 1–100 μm, are milky white and opaque liquids, and are thermodynamically and kinetically unstable systems. Therefore, it is of great significance to reduce the emulsifier content and develop submicroemulsions with simple composition, thermodynamic stability, and good spreadability, dispersibility, and long-lasting moisturizing properties. To this end, this invention is proposed. Summary of the Invention
[0004] In view of the aforementioned state of the prior art, this invention further studies and improves upon previous nanoemulsions for string maintenance, providing a submicron emulsion for musical instrument maintenance and its preparation method. This submicron emulsion has a particle size of 50-900 nm, is a milky white, slightly bluish, opaque emulsion, has a simple composition, mild properties, thermodynamic stability, and is not prone to stratification. It also possesses good spreadability, dispersibility, and long-lasting moisturizing properties, making it suitable for both deep cleaning and daily maintenance of musical instrument surfaces.
[0005] The technical solution of the present invention is as follows:
[0006] A musical instrument conditioning microemulsion comprises the following components by weight percentage:
[0007] The mixture contains 6%–8% compound emulsifier, co-emulsifier, 21%–27% liquid paraffin, 0%–2% glyceryl monostearate, 0.1%–0.2% xanthan gum, and the balance water. The compound emulsifier, by mass percentage, consists of 53%–62% Tween 80 and 38%–47% Span 80. The mass ratio of compound emulsifier to co-emulsifier is K. m Value controls the amount of co-emulsifier used, K m The ratio is 2:1, and the co-emulsifier is glycerin.
[0008] According to the present invention, preferably, the composite emulsifier has an HLB value of 9-11, more preferably 10-11.
[0009] According to the present invention, preferably, the instrument care submicroemulsion comprises the following components by weight percentage:
[0010] The compound emulsifier comprises 6.2%–7.5%, glycerin 3.2%–3.7%, liquid paraffin 22%–25%, glyceryl monostearate 0.5%–2%, xanthan gum 0.15%–0.2%, and the balance being water. The compound emulsifier, by mass percentage, consists of 53%–62% Tween 80 and 38%–47% Span 80.
[0011] According to the present invention, preferably, the instrument care submicroemulsion comprises the following components by weight percentage:
[0012] The compound emulsifier consists of 6.5% compound emulsifier, 3.25% glycerol, 23.4% liquid paraffin, 1%~1.5% glyceryl monostearate, 0.2% xanthan gum, and the balance being water. The compound emulsifier is composed of 53%~62% Tween 80 and 38%~47% Span 80 by mass percentage.
[0013] According to the present invention, preferably, the instrument care submicroemulsion comprises the following components by weight percentage:
[0014] The compound emulsifier comprises 6.5% glycerin, 3.25% glycerol, 23.4% liquid paraffin, 1% glyceryl monostearate, 0.2% xanthan gum, and the balance being water. The compound emulsifier consists of 58% Tween 80 and 42% Span 80 by weight percentage.
[0015] According to the present invention, the preparation method of the above-mentioned instrument maintenance submicroemulsion includes the following steps:
[0016] Preparation of composite emulsifier: Tween 80 and Span 80 are mixed and stirred evenly to obtain composite emulsifier;
[0017] Preparation of the aqueous phase: Xanthan gum and glycerol are mixed and stirred until there are no powder particles. Water is added and stirred until fully swollen. The mixture is then heated in a water bath at 70-80°C to obtain the aqueous phase.
[0018] Preparation of the oil phase: Glyceryl monostearate, composite emulsifier and liquid paraffin are mixed and dissolved by stirring in a water bath at 70~80℃ to obtain the oil phase;
[0019] Emulsification: The aqueous phase is added dropwise to the oil phase in a constant temperature water bath at 70~80℃, stirred until fully emulsified, and then cooled to obtain the instrument maintenance microemulsion.
[0020] According to the present invention, preferably, in the preparation of the aqueous phase, after xanthan gum and glycerin are mixed and stirred evenly, a portion of water is first added and stirred until fully swollen, then the remaining water is added, shaken and waited for 5 minutes, and then heated in a water bath at 70~80℃ for 10 minutes to obtain the aqueous phase.
[0021] According to the present invention, preferably, the oil phase is dissolved by stirring in a water bath at 70~80°C for 10 min during preparation.
[0022] According to the present invention, preferably, during the emulsification process, stirring and emulsification are carried out for 30 minutes.
[0023] The present invention has the following beneficial effects:
[0024] 1. The instrument maintenance microemulsion of the present invention is a nano-sized emulsion. The ultra-small particle size can significantly delay aggregation or stratification, so that the microemulsion can maintain physical stability for months or even years, has thermodynamic stability, and does not exhibit flocculation or agglomeration.
[0025] 2. The microemulsion of the present invention has a simple composition, consisting only of deionized water, glycerol, xanthan gum, glyceryl monostearate, liquid paraffin, Tween 80, and Span 80. The process is simple and easy for large-scale industrial production.
[0026] 3. Each component of this invention is mild in nature, possessing excellent spreadability, dispersibility, and long-lasting moisturizing properties. It does not damage the lacquer, keys, or strings of musical instruments, and can be used for both deep cleaning and deep nourishment. Attached Figure Description
[0027] Figure 1 The graph shows the changes of emulsions with different HLB values over time: a) after 0 h; b) after 6 h; c) after 21 h; d) after 43 h; e) after 72 h.
[0028] Figure 2 For different K m Lower breast area map, a) K m =1:0; b)K m =1:1; c)K m =1:2; d)K m =2:1.
[0029] Figure 3 The appearance, color, average particle size, and PDI diagram of emulsions obtained with different mass fractions of composite emulsifiers are shown.
[0030] Figure 4 Appearance, color, average particle size, and PDI diagram of emulsions obtained with different mass fractions of liquid paraffin.
[0031] Figure 5 Appearance, color, average particle size, and PDI diagram of emulsions obtained with different mass fractions of glyceryl monostearate (GMS).
[0032] Figure 6 The appearance, color, average particle size, and PDI diagram of emulsions obtained with different mass fractions of xanthan gum are shown.
[0033] Figure 7 Photographs of the emulsion obtained from the response surface optimization experiment.
[0034] Figure 8 The images show the appearance and particle size distribution of the submicroemulsion prepared according to the optimal formulation, where: a) appearance; b) particle size distribution.
[0035] Figure 9 The particle size distribution diagram is shown for the submicroemulsion prepared in Example 1 after centrifugation.
[0036] Figure 10 The average particle size and PDI diagrams of the submicron emulsion prepared in Example 1 after heating at different temperatures are shown.
[0037] Figure 11 The average particle size and PDI of the submicron emulsion prepared in Example 1 at different storage temperatures are shown in the diagram.
[0038] Figure 12 The diagram shows the identification of submicroemulsion structure types using the dilution method in Experiment Example 2, a) diluted with liquid paraffin; b) diluted with water.
[0039] Figure 13 The images shown are TEM images of the submicroemulsion prepared in Example 1, where: a) magnification × 2000; b) magnification × 5000. Detailed Implementation
[0040] This invention provides a submicroemulsion for musical instrument care and its preparation method. The submicroemulsion exhibits thermodynamic stability, is not prone to delamination, and possesses excellent spreadability, dispersibility, and long-lasting moisturizing properties. It solves the problems of traditional instrument care products corroding the instrument's lacquer and key skin, and damaging the protective layer with long-term use, enabling deep cleaning and daily maintenance of the instrument's surface.
[0041] The instrument care microemulsion of the present invention comprises the following components by weight percentage:
[0042] The mixture contains 6%–8% compound emulsifier, co-emulsifier, 21%–27% liquid paraffin, 0%–2% glyceryl monostearate, 0.1%–0.2% xanthan gum, and the balance water. The compound emulsifier, by mass percentage, consists of 53%–62% Tween 80 and 38%–47% Span 80. The mass ratio of compound emulsifier to co-emulsifier is K. m Value controls the amount of co-emulsifier used, K m The ratio is 2:1, and the co-emulsifier is glycerin.
[0043] According to the present invention, the preferred microemulsion formulation is carried out according to the following process:
[0044] 1. Screening of HLB values for composite emulsifiers
[0045] Method: Emulsifiers with HLB values between 8 and 18 are suitable for preparing water-in-oil (O / W) emulsions. Different emulsifiers, when combined, can facilitate emulsification. According to... Emulsifiers with different HLB values were prepared, as shown in Table 1.
[0046] Table 1. Emulsifiers and their HLB values
[0047]
[0048] Take eight 15 mL centrifuge tubes and add 0.1 g of liquid paraffin and 3 g of emulsifiers with different HLB values to each. After vigorous shaking for 10 seconds, add 2 mL of distilled water, shake well, and then add another 4.5 mL of distilled water along the wall. Shake the resulting emulsion thoroughly for 3 minutes and let it stand. Observe the layering phenomenon at 6 h, 21 h, 43 h, and 72 h, and record the layer height. The changes of emulsions with different HLB values over time are shown in the graph below. Figure 1 As shown, where: a) after 0 h; b) after 6 h; c) after 21 h; d) after 43 h; e) after 72 h.
[0049] Results: Flocculation occurred when the HLB value was 4.3, possibly due to the emulsifier being excessively lipophilic and unable to effectively reduce the oil-water interfacial tension. At HLB values of 13-14 and 15, the color turned yellow and oil-water separation was easy, possibly due to the emulsifier being excessively hydrophilic and unable to form a stable oil-water interfacial film. At HLB values of 8-9, 12-13, and 11-12, the emulsion was uniformly white but easily separated, possibly due to weak interfacial film strength and poor emulsification. At HLB values of 9-10 and 10-11, the emulsion was uniformly white and did not easily separate, with the separation height decreasing sequentially. Therefore, the composite emulsifier showed the best emulsion stability and highest emulsification efficiency when the HLB value was 10-11.
[0050] 2. Ratio of compound emulsifier to co-emulsifier (K) m Filtering by value
[0051] Methods: Based on the results obtained from HLB value exploration, the optimal HLB value range is 10-11. The oil phase is liquid paraffin, the aqueous phase is distilled water, and the co-emulsifier is glycerol. K... m Pseudo-ternary phase diagrams with values of 1:0, 1:1, 1:2, and 2:1.
[0052] Mixed emulsifiers (compound emulsifiers and co-emulsifiers according to K) m The emulsion was mixed with liquid paraffin in ratios of 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, and 1:9 (w / w), respectively, and magnetically stirred to form a homogeneous oil phase. At room temperature, distilled water was slowly and uniformly added dropwise to the continuously stirred oil phase until the emulsion changed from clear to cloudy. The total volume of the aqueous phase used to change the emulsion from clear to cloudy was recorded, and the desired state was a white emulsion with a bluish opalescence. A pseudo-three-phase diagram was plotted using the mass fractions of the composite emulsifier, oil phase, and aqueous phase at the critical point of cloudiness. The area of the closed region enclosed by each critical point and the aqueous phase vertex in the pseudo-three-phase diagram was used to evaluate the ability to form submicroemulsions under these conditions. The larger the area, the stronger the ability to form submicroemulsions under these conditions, indicating optimal conditions. Different K... m The area of the breast region is shown in the figure below. Figure 2 As shown, where: a) K m =1:0; b)Km =1:1; c)K m =1:2; d)K m =2:1.
[0053] Result: When K m The submicron emulsion area is smallest when the ratio is 1:0, indicating that the co-emulsifier glycerol can indeed expand the submicron emulsion area. m As the ratio increases from 1:2 to 2:1, the submicron emulsion region gradually enlarges, K m The K value affects the fluidity and elasticity of the interfacial membrane; choosing an appropriate K value is crucial. m The value can more efficiently promote the formation of submicroemulsions. The maximum oil-phase solubilization effect can be achieved when the co-emulsifier is fully embedded in the composite emulsifier. Results show that K... m When the ratio is 2:1, the area of the submicroemulsion is the largest, therefore K m Choose a value of 2:1.
[0054] 3. Effect of the mass fraction of composite emulsifier on the emulsion
[0055] Methods: The experimental design is shown in Table 2. The average particle size and PDI of the emulsions obtained in each group were measured. All experiments were performed in triplicate.
[0056] Table 2. Exploration of the mass fraction of composite emulsifiers
[0057]
[0058] The appearance, color, average particle size, and PDI of emulsions obtained with different mass fractions of composite emulsifiers are shown in the figure below. Figure 3 As shown.
[0059] Results: The mass fraction of the composite emulsifier affected the appearance, color, average particle size, and dispersion uniformity of the emulsion, exhibiting a clear and regular pattern. As the mass fraction of the composite emulsifier increased, the color of the emulsion changed from milky white and bluish-white to translucent, and the average particle size of the emulsion also decreased continuously, while the PDI (particulate density) generally showed a trend of first decreasing and then increasing.
[0060] At 5%, it is milky white with the highest PDI (>0.3). This may be because the emulsifier content is low, the oil-water interface is not fully covered, and the droplets are prone to coalescence and Ostwald ripening, forming a coarse emulsion. At this time, the emulsion particles are large and widely distributed, and the visible light is mainly reflected and scattered.
[0061] Within a variation range of 6% to 8%, the emulsion is white with a bluish tint and is opaque. The average particle size of the emulsion is between 94 nm and 129 nm, and the PDI is relatively small. This may be because the particle size of the emulsion is reduced to the submicroemulsion range, and the droplets produce a significant Tyndall effect on short-wavelength blue light.
[0062] Within a range of 10% to 14%, the emulsion is semi-transparent, with an average particle size fluctuating between 61 nm and 78 nm. The PDI is relatively low, possibly due to a high emulsifier content, which reduces the emulsion particle size to the microemulsion range.
[0063] Therefore, the mass fraction level of the composite emulsifier selected for the response surface methodology was 6%-8%.
[0064] 4. Effect of liquid paraffin mass fraction on emulsion
[0065] Methods: Based on the experimental results of the effect of the mass fraction of composite emulsifier on the emulsion, the experimental design is shown in Table 3. The average particle size and PDI of the emulsions obtained in each group were measured. All experiments were performed in triplicate.
[0066] Table 3. Investigation of mass fraction of liquid paraffin
[0067]
[0068] The appearance, color, average particle size, and PDI of emulsions obtained from liquid paraffin with different mass fractions are shown in the figure. Figure 4 As shown.
[0069] Results: The mass fraction of liquid paraffin affected the appearance, average particle size, and PDI of the emulsion. With a fixed mass fraction of 7% for the composite emulsifier, the average particle size of the emulsion gradually increased with increasing liquid paraffin mass fraction, while the PDI initially decreased and then increased.
[0070] When the mass fraction of liquid paraffin is 6%, the average particle size is the largest and the PDI is >0.3. Under this condition, the oil phase content is too low, and the 7% composite emulsifier is excessive for the small amount of oil phase. This causes the excess emulsifier to be unable to be effectively adsorbed at the oil-water interface and to exist in the continuous phase in the form of micelles, resulting in larger particle size. At the same time, the limited oil phase volume is difficult to support the emulsifier to form a dense and stable interfacial film. Flocculation and Austronesian ripening easily occur between droplets, resulting in a wider particle size distribution. Therefore, a white coarse emulsion is formed.
[0071] When the mass fraction of liquid paraffin increases to 12%, the oil phase volume is well matched with the 7% composite emulsifier. The emulsifier can reach a saturated adsorption state at the interface, effectively reducing interfacial tension and forming a stable interfacial film. At this time, the PDI is reduced to the minimum and the particle size distribution is the most uniform.
[0072] However, when the mass fraction of liquid paraffin continued to increase to 30%, the oil phase volume became too large, and 7% emulsifier was insufficient to completely cover the surface of all oil droplets. The interfacial coverage density began to decrease, and some oil droplets agglomerated due to interfacial film defects, resulting in an increase in average particle size. At the same time, the PDI increased again.
[0073] Therefore, to ensure that the response surface methodology yields a submicroemulsion system with uniform particle size and good stability, the range of liquid paraffin mass fraction was selected to be 21%–27%. This range avoids the region of relative emulsifier excess caused by low oil phase content, while also being far from the region of insufficient emulsifier under high oil phase content. This ensures that the emulsifier and oil phase are in a more suitable ratio range, which is beneficial for the establishment of subsequent optimization models and formulation screening.
[0074] 5. Effect of glyceryl monostearate mass fraction on emulsion
[0075] Methods: Based on the experimental results of the mass fraction of composite emulsifier and liquid paraffin, the experiment was designed as shown in Table 4. The average particle size and PDI of the emulsions obtained in each group were measured. All experiments were performed in triplicate.
[0076] Table 4. Exploration of the mass fraction of glyceryl monostearate
[0077]
[0078] The appearance, color, average particle size, and PDI of emulsions obtained with different mass fractions of glyceryl monostearate (GMS) are shown in the figure below. Figure 5 As shown.
[0079] Results: Except for the blue-white color when the mass fraction of glyceryl monostearate was 1%, all the others were milky white. The effect of glyceryl monostearate on the particle size of the emulsion also showed a trend of first decreasing and then increasing.
[0080] When the amount of glyceryl monostearate is low, its molecules form a dense and ordered interfacial film at the oil-water interface, effectively reducing interfacial tension and preventing droplet aggregation, thus gradually reducing the particle size. When the amount reaches the optimal value (1%), the mechanical strength and density of the interfacial film are at their best, resulting in the smallest emulsion particle size and the best uniform dispersion.
[0081] When the amount of glyceryl monostearate continues to increase to more than 2%, excessive glyceryl monostearate molecules may accumulate excessively at the interface, leading to an increase in the thickness and rigidity of the interfacial film, which is not conducive to shear refinement during the emulsification process. At the same time, excessive glyceryl monostearate forms a large number of lamellar liquid crystal phases in water, which causes the viscosity of the system to increase sharply, hindering the effective shear dispersion of the oil phase by the emulsification equipment, resulting in insufficient droplet refinement, and even causing flocculation and aggregation between droplets, thus significantly increasing the particle size.
[0082] Since the effective range of glyceryl monostearate mass fraction is narrow and the optimal value is relatively clear, it is not considered as an influencing factor in response surface methodology. Instead, the 1% value determined by this method is used in subsequent experiments.
[0083] 6. Effect of xanthan gum mass fraction on emulsion
[0084] Methods: Based on the results obtained from screening the mass fractions of compound emulsifier, liquid paraffin and glyceryl monostearate, the experimental design is shown in Table 5. The average particle size and PDI of the emulsions obtained in each group were determined, and all experiments were performed in triplicate.
[0085] Table 5. Exploration of Xanthan Gum Mass Fraction
[0086]
[0087] The appearance, color, average particle size, and PDI of emulsions obtained with different mass fractions of xanthan gum are shown in the figure below. Figure 6 As shown.
[0088] Results: Within the xanthan gum mass fraction range of 0%–0.3%, the emulsions were all bluish-white, with little variation in average particle size (100–200 nm) and PDI (<0.3). As a stabilizer, xanthan gum significantly increased the viscosity of the aqueous phase, reducing the Brownian motion velocity and collision frequency of the emulsion droplets, thereby inhibiting droplet aggregation and sedimentation. Its effect on emulsion particle size was not significant. Therefore, the xanthan gum mass fraction was not considered as an influencing factor in response surface methodology, and a xanthan gum mass fraction of 0.2% was used in subsequent experiments.
[0089] 7. Response Surface Optimization Experiment
[0090] Based on the results of the single-factor experiments, response surface methodology was designed and data analyzed using Design Expert 13.0 software. Using the average particle size of the submicron emulsion as the response value, the mass fraction of the composite emulsifier, the mass fraction of liquid paraffin, and the HLB value were selected as influencing factors. A three-factor, three-level response surface methodology was designed, as shown in Tables 6 and 7.
[0091] Table 6 Factor and Level Coding Table
[0092]
[0093] Table 7 Response Surface Experimental Design and Results
[0094]
[0095] Photographs of the emulsion obtained from the response surface optimization experiment are shown below. Figure 7 As shown.
[0096] Response surface regression analysis was performed using Design-Expert 13.0 software, yielding the regression equation: Average particle size Y = 175.633 - 18.5375A + 2.40B - 16.8625C - 1.50AB - 2.925AC + 6.20BC - 9.60417A 2 -15.4292B 2 -16.2042C 2
[0097] As shown in Table 8, the overall P < 0.0001 indicates that the regression model is highly significant and can be used for prediction and optimization. In the first-order terms, the mass fraction of the composite emulsifier (A), the mass fraction of liquid paraffin (B), and the HLB value (C) all have a significant impact on the average particle size of the submicron emulsion (P < 0.05), with A and C being extremely significant (P < 0.0001). Only BC in the interaction terms is significant, suggesting that the interaction between the factors may be relatively small. All quadratic terms are extremely significant, indicating that the relationship between the three factors and Y is not a simple linear one, but a curvilinear one, suggesting the existence of an optimal value point. The lack-of-fit term is insignificant, indicating that the interference from unknown factors is minimal, and the experimental results are reliable.
[0098] Table 8. Analysis of variance (ANOVA) of each term in the regression equation.
[0099]
[0100] The mass fraction of the composite emulsifier had the most significant effect on the average particle size, followed by the mass fraction of liquid paraffin, and finally the HLB value.
[0101] The optimal formulation for preparing submicroemulsions, determined by response surface methodology, is as follows: 6.5% composite emulsifier (mass fraction), 23.4% liquid paraffin (mass fraction), and HLB value of 10.7. Three parallel emulsions were prepared according to the optimized formulation, and their particle size ranges were determined. The particle size distribution is shown in Table 9.
[0102] Table 9. Particle size table for optimal submicroemulsion formulations
[0103]
[0104] Appearance and particle size distribution of the submicroemulsion prepared according to the optimal formulation are shown in the following figures. Figure 8 As shown, where: a) appearance diagram; b) particle size diagram.
[0105] Depend on Figure 8 It is known that the appearance is white with a bluish sheen and opaque. The particle size range is mainly 50.79~568.3 nm, and the calculated average particle size is 158.6 ± 4.704 nm, which is consistent with the submicron emulsion particle size range; the PDI is 0.1926 ± 0.0145.
[0106] According to the present invention, the preparation method of the above-mentioned instrument maintenance submicroemulsion includes the following steps:
[0107] Preparation of composite emulsifier: Tween 80 and Span 80 are mixed and stirred evenly to obtain composite emulsifier;
[0108] Preparation of the aqueous phase: Xanthan gum and glycerol are mixed and stirred until there are no powder particles. Water is added and stirred until fully swollen. The mixture is then heated in a water bath at 70-80°C to obtain the aqueous phase.
[0109] Preparation of the oil phase: Glyceryl monostearate, composite emulsifier and liquid paraffin are mixed and dissolved by stirring in a water bath at 70~80℃ to obtain the oil phase;
[0110] Emulsification: The aqueous phase is added dropwise to the oil phase in a constant temperature water bath at 70~80℃, stirred until fully emulsified, and then cooled to obtain the instrument maintenance microemulsion.
[0111] In one or more preferred embodiments, the aqueous phase preparation process involves mixing xanthan gum and glycerin until homogeneous, then adding a portion of water and stirring until fully swollen. The remaining water is then added, shaken, and allowed to stand for 5 minutes. The mixture is then heated in a water bath at 70-80°C for 10 minutes to obtain the aqueous phase. Preferably, the oil phase preparation process involves stirring and dissolving in a water bath at 70-80°C for 10 minutes. Preferably, the emulsification process involves stirring and emulsifying for 30 minutes.
[0112] The technical solution of the present invention will be clearly and completely described below through specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other implementation cases obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0113] Examples 1-5
[0114] The preparation of the instrument maintenance microemulsion uses liquid paraffin, Tween 80, Span 80, glycerin, glyceryl monostearate, xanthan gum, and distilled water as raw materials. The specific formula is shown in Table 10.
[0115] The preparation process includes:
[0116] (1) Preparation of composite emulsifier: Add Tween 80 and Span 80 to a 250mL flask and stir at 600 rpm for 5 min at room temperature to obtain composite emulsifier.
[0117] (2) Preparation of aqueous phase: Add xanthan gum and glycerol to a 250mL flask and stir with a glass rod until there are no white powder particles and the mixture is transparent paste. First, add 10mL of distilled water and stir at room temperature until fully swollen. Then add the remaining distilled water, shake gently, wait at room temperature for 5 minutes, and then heat in a water bath at 70~80℃ for 10 minutes to obtain the aqueous phase.
[0118] (3) Preparation of oil phase: Add glyceryl monostearate, the prepared composite emulsifier and liquid paraffin to a 250mL flask, stir and dissolve in a water bath at 70~80℃ for 10 min to obtain the oil phase.
[0119] (4) Emulsification: The aqueous phase is slowly added drop by drop to the oil phase in a constant temperature water bath at 70~80℃, stirred at 1400 rpm for 30 min, and cooled to obtain the instrument maintenance microemulsion.
[0120] Table 10 Specific formulations of Examples 1-5
[0121]
[0122] Experimental Example 1: Stability of Submicron Emulsions
[0123] 1. Centrifugal stability
[0124] Method: The submicron emulsion prepared in Example 1 was centrifuged at 4000 rpm for 15 min. The appearance was observed, and the average particle size and PDI of the unseparated emulsion after centrifugation were measured. Figure 9 As shown.
[0125] Results: The prepared submicroemulsion exhibited good centrifugal stability. No significant changes in appearance were observed after centrifugation at 4000 rpm; the average particle size was measured to be 157.2 nm, essentially unchanged from before centrifugation, indicating that the submicroemulsion could maintain a stable dispersion under 4000 rpm centrifugation conditions. The small particle size of the submicroemulsion is beneficial to kinetic stability; that is, even under high-speed centrifugation, the increased Stokes settling force on the droplets maintains the synergistic stability of the interfacial film and the viscous resistance of the continuous phase, preventing separation.
[0126] 2. Thermal stability
[0127] Methods: The submicron emulsion prepared in Example 1 was placed in water baths at 70℃, 80℃, and 90℃ for 20 min, respectively. The average particle size and PDI of the emulsions after heating at different temperatures were measured. Figure 10 As shown.
[0128] Results: The particle size and PDI of the prepared submicroemulsion remained stable after heat treatment at 70℃, but the particle size and PDI increased to varying degrees after heating at 80℃ and 90℃. This may be because the emulsion can maintain a stable dispersion at 70℃, but at 80℃, due to factors such as emulsifier desorption, changes in interfacial tension, decrease in oil phase viscosity, or intensified Austronesian ripening, the emulsion structure is disrupted, resulting in an increase in average particle size and a wider particle size distribution. Therefore, the heating temperature should not exceed 70℃.
[0129] 3. Storage stability
[0130] Methods: Three groups of submicron emulsions were taken and placed in environments of -20℃, 25℃, and 40℃ respectively. The average particle size and PDI of the emulsions were measured at different times. Figure 11 As shown.
[0131] Results: The particle size of the prepared submicroemulsion showed minimal variation under storage conditions of -20℃, 25℃, and 40℃, with no obvious increasing trend. This indicates that the submicroemulsion has good long-term storage stability over a wide temperature range, providing reliable quality assurance for its subsequent storage, transportation, and application.
[0132] Experimental Example 2: Morphological Evaluation
[0133] 1. Identification of the type of microemulsion
[0134] Methods: The structural type of submicroemulsion was identified using the dilution method. The dilution method involves diluting the submicroemulsion separately with distilled water and liquid paraffin. If it can be diluted with a large amount of distilled water, it is an O / W type submicroemulsion; if it is diluted with a large amount of liquid paraffin, it is a W / O type submicroemulsion. Take 6 mL each of distilled water and liquid paraffin, add an equal volume of submicroemulsion to each, shake gently, and observe the state of the system. Figure 12 As shown.
[0135] Results: The prepared submicroemulsion sank into particles in liquid paraffin, but quickly and evenly mixed with distilled water. Therefore, the submicroemulsion prepared in this experiment was of the O / W type.
[0136] 2. Morphological observation of submicroemulsions
[0137] Methods: The submicron emulsion was diluted 50 times and dropped onto a copper grid. After evaporation and drying at room temperature for 7 days, the morphology of the emulsion was observed by transmission electron microscopy.
[0138] Results: The submicron emulsion prepared in Example 1 was diluted 50 times, dropped onto a copper grid, dried, and then its morphology was observed by transmission electron microscopy (TEM). Figure 13 As shown, the droplets are approximately spherical in appearance, with a diameter ranging from 60 to 600 nm, which matches the droplet size distribution range measured by the particle size analyzer and falls within the category of submicroemulsions.
Claims
1. A microemulsion for musical instrument care, characterized in that, This submicroemulsion comprises the following components by weight percentage: The mixture contains 6%–8% compound emulsifier, co-emulsifier, 21%–27% liquid paraffin, 0.5%–2% glyceryl monostearate, 0.1%–0.2% xanthan gum, and the balance being water. The compound emulsifier, by mass percentage, consists of 53%–62% Tween 80 and 38%–47% Span 80. The mass ratio of compound emulsifier to co-emulsifier is... K m The amount of co-emulsifier used should be controlled. K m The ratio is 2:1, and the co-emulsifier is glycerin.
2. The instrument preservation microemulsion according to claim 1, characterized in that, The HLB value of the composite emulsifier is 9-11.
3. The instrument preservation microemulsion according to claim 1, characterized in that, The instrument care submicroemulsion comprises the following components by weight percentage: The compound emulsifier comprises 6.2%–7.5%, glycerin 3.2%–3.7%, liquid paraffin 22%–25%, glyceryl monostearate 0.5%–2%, xanthan gum 0.15%–0.2%, and the balance being water. By mass percentage, the compound emulsifier consists of 53%–62% Tween 80 and 38%–47% Span 80.
4. The instrument preservation microemulsion according to claim 1, characterized in that, The instrument care submicroemulsion comprises the following components by weight percentage: The compound emulsifier consists of 6.5% compound emulsifier, 3.25% glycerol, 23.4% liquid paraffin, 1% glyceryl monostearate, 0.2% xanthan gum, and the balance being water. The compound emulsifier is composed of 53%–62% Tween 80 and 38%–47% Span 80 by mass percentage.
5. The instrument preservation microemulsion according to claim 1, characterized in that, The instrument care submicroemulsion comprises the following components by weight percentage: The compound emulsifier comprises 6.5% glycerin, 3.25% glycerol, 23.4% liquid paraffin, 1% glyceryl monostearate, 0.2% xanthan gum, and the balance being water. The compound emulsifier consists of 58% Tween 80 and 42% Span 80 by weight percentage.
6. The method for preparing the instrument maintenance submicroemulsion according to any one of claims 1-5, characterized in that, The steps include the following: Preparation of composite emulsifier: Tween 80 and Span 80 are mixed and stirred evenly to obtain composite emulsifier; Preparation of the aqueous phase: Xanthan gum and glycerol were mixed and stirred until there were no powder particles. Water was added and stirred until fully swollen. The mixture was then heated in a water bath at 70-80°C to obtain the aqueous phase. Preparation of the oil phase: Glyceryl monostearate, composite emulsifier and liquid paraffin are mixed and dissolved by stirring in a water bath at 70~80℃ to obtain the oil phase; Emulsification: The aqueous phase is added dropwise to the oil phase in a constant temperature water bath at 70~80℃, stirred until fully emulsified, and then cooled to obtain the instrument maintenance microemulsion.
7. The method for preparing the instrument maintenance submicroemulsion according to claim 6, characterized in that, In the preparation of the aqueous phase, after the xanthan gum and glycerol are mixed and stirred evenly, a portion of water is added and stirred until fully swollen. Then, the remaining water is added, shaken and waited for 5 minutes. The aqueous phase is then obtained by heating in a water bath at 70-80°C for 10 minutes.
8. The method for preparing the instrument maintenance submicroemulsion according to claim 6, characterized in that, During the preparation of the oil phase, it is dissolved by stirring in a water bath at 70~80℃ for 10 min.
9. The method for preparing the instrument maintenance submicroemulsion according to claim 6, characterized in that, During the emulsification process, stir and emulsify for 30 minutes.
Citation Information
Patent Citations
String maintenance nano-emulsion and preparation method thereof
CN120554858A